Low occurrence of Cryptosporidium canis in feces of dogs seroreactive for Leishmania spp. - Lemus, Sara do Nascimento; Mourao, Luis Paulo Bueno; Ferrari, Elis Domingos [UNESP]; Bresciani, Katia Denise Saraiva [UNESP]; Silveira Neto, Luiz da; Pimenta, Raphael Sanzio (Univ Estadual Londrina, 2022)
In this study, we investigated the occurrence and characterized molecularly Cryptosporidium oocysts in feces of dogs seroreactive for Leishmania spp. We hypothesized that the clinical staging of canine visceral leishmaniasis (CVL) influences the occurrence and intensity of Cryptosporidium spp. oocyst shedding in feces from the canine host due to the immunosuppression induced by Leishmania infantum. Fecal samples from 101 dogs with anti-Leishmania spp. antibodies detected by Dual-Path Platform (DPP (R)) immunochromatographic test (Biomanguinhos) and/or enzyme-linked immunosorbent assay (Biomanguinhos) were concentrated by the centrifuge-sedimentation method in water-ethyl acetate. The sediments were submitted to the technique of negative staining with malachite green and observed under an optical microscope (400x magnification). The occurrence was 0.99% (95 confidence interval 0.00%-2.93%). A single Cryptosporidium oocyst was found in one of the samples examined by microscopy, and the result was confirmed by nested-PCR. The amplicon sequence showed 100% genetic identity with Cryptosporidium canis. The dog presented the following clinical signs suggestive of CVL: cachexia, generalized alopecia, pale colored gingival mucosa, splenomegaly, and onychogryphosis. We conclude that there is no evidence that the oligosymptomatic and symptomatic clinical staging of dogs seroreactive for Leishmania spp. influenced the occurrence and intensity of C. canis oocyst shedding in the canine host.
Keywords: Cryptosporidiosis; Epidemiology; Leishmaniasis; One health; Zoonosis